Confronting climate crises through education : reading our way forward - Young, Rebecca L. (Ecocritical theory and practice., 2018)
Confronting Climate Crises through Education: Reading Our Way Forward examines ways fiction and non-fiction can shape an instructional lens designed to witness the environmental crises we face both culturally and globally while fostering a more ecologically conscious, globally-minded student body prepared to confront them.